Hydroclimatic changes since the Last Glacial Maximum recorded in mountain peat deposit on the southwestern margin of the Sichuan Basin, China - Huang, Ming; Deng, Yunkai; Peng, Haijun; Wen, Zhenming; Shang, Guangchun; Guan, Houchun; Ma, Chunmei (Frontiers in Ecology and Evolution, 2022)
Knowledge of the hydroclimatic changes in Southwest China since the Last Glacial Maximum (LGM) is crucial for disentangling the long-term evolution of the Asia Monsoon and predicting the future fate of the mountain peat deposit in the Asia Monsoon region. In this study, we obtained a 530-cm-long peat core from the Ganchi wetland in Southwest China and analyzed its geochemical indices, including total nitrogen (TN), total organic carbon (TOC), stable carbon isotope composition of organics (δ13Corg), and the concentration of several major elements, to investigate the sedimentary and hydroclimate evolution since the LGM. We found that the peat strata in the Ganchi wetland have developed gradually from 13.7 cal kyr BP, which is likely ascribed to the warm climate during the Bølling-Allerød (B/A) period. TOC, δ13Corg, K/Ti, and Fe/Mn records showed notable paleoclimate shifts since the last deglaciation. The first warming period after the LGM was observed starting at 18.2 cal kyr BP, which is consistent with other records from Southwest China. The reconstruction results show that the western margin of the Sichuan Basin during the last deglaciation was most affected by the East Asia summer monsoon (EASM), and less affected by the Indian summer monsoon (ISM) . The climate of the early Holocene (11.2–7.5 cal kyr BP) was affected by both the ISM and EASM, resulting in more complex local climatic features. The Holocene Megathermal period observed from 7.5–3.5 cal kyr BP, is consistent with the timing detected in other records of Southwest China.